Numerical modelling of web crippling failures in cold-formed steel unlipped channel sections - Janarthanan, B.; Mahendran, M.; Gunalan, S. (Elsevier, 2019)
This paper presents a finite element analysis based study of web crippling failures in cold-formed steel unlipped channel sections with their flanges fastened to supports under one-flange load cases (EOF and IOF). Currently no design equations are available in the current cold-formed steel specifications to determine the web crippling capacities of unlipped channel sections with restrained flanges under one flange load cases. Hence the web crippling behaviour of unlipped channel sections was first investigated experimentally using 28 tests and suitable coefficientswere proposed for the currentweb crippling design equation. However, the applicability of the proposed coefficients was limited to the tested channel sections. In this study advanced finite element models were developed in ABAQUS/CAE and validated in terms of ultimate failure loads, load versus deflection curves and failure modes. The developed models were analysed using nonlinear static and quasi-static analysis based on implicit and explicit integration schemes. This study addressed the effects ofmesh size, element type,mechanical property model and inertia of support and loading plates. Also, the effects of two enhancement techniques of explicit analysis such asmass scaling and artificial loading rateswith different thicknesseswere investigated and the results are presented. A detailed parametric study was then conducted using the validated finite element models. New and improved design equations were proposed to determine the web crippling capacities of unipped channel sections using the results from both finite element analysis based parametric study and experiments.
Keywords: Cold-formed steel; Unlipped channels; Web crippling failure; Finite element analysis